Growth and Feed Efficiency of Red Tilapia (Oreochromis sp.) Reared in Different Salinities - Setiawati, Mia; Suprayudi, M. Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
The objective of this research was to know the effect of salinity on the growth and utilized of feed energy by red tilapia, Oreochromis sp. Four fishes with 4,15-4,42 g initial body weights were cultured in a 50x40x35 cm aquarium for 40 days. Fish were fed on these diets three times a day at satiation. Dietary growth rate, feed efficiency, protein and lipid retention increased with increasing salinity (p